PEMBERDAYAAN MASYARAKAT SEKTOR PERTANIAN BERKELANJUTAN TERHADAP PENDAPATAN PETANI DESA PENYANGGA: TINJAUAN LITERATUR - Ngga'a, Christin Yudith Wahyuni; Haryanto, Tri (AGRICA, 2025)
Poverty and low productivity of agricultural businesses in buffer villages are two interrelated conditions, including the suboptimal increase in income in the buffer villages of the Kelimutu National Park Area. Various empowerment programs are expected to improve these conditions. This article aims to review the socio-economic aspects of farmers that influence the increase in farmer income in the buffer village. This study seeks to understand the essence of the entity so that it can underlie policies that improve conditions and indicators that will be used to measure conditions for good policy making. The study method uses literature studies for conceptual studies and journal reviews from Scopus, Google Scholar, ScienceDirect, Frontiers and Sinta-accredited journals, as well as secondary data. Defining the nature, characteristics and essence of scientific and socio-economic aspects of increasing income from the farmer's perspective is very necessary to reveal the essential aspects for increasing this income. The results of the study reveal that the economic empowerment of communities and agricultural income in buffer villages includes dimensions of access to land resources, capital and technology, increasing farmer capacity in the form of training and mentoring, developing farmer institutions in farmer group forums, implementing sustainable agricultural practices in the form of organic fertilisers, and land conservation and government policies.